Short report: Melioidosis in Myanmar: forgotten but not gone? - Wuthiekanun, V; Langa, S; Swaddiwudhipong, W; Jedsadapanpong, W; Kaengnet, Y; Chierakul, W; Day, N; Peacock, S (2006)
A serologic survey of adults resident in Myanmar was conducted to define the presence of antibodies to Burkholderia pseudomallei, the cause of melioidosis. Antibodies were detectable by indirect hemagglutination assay (IHA) in 757 (78%) of 968 adults, of whom 69 (7%) had an IHA titer > or =1:160.